Beyond the rhetoric: How can non-government organisations contribute to reducing health disparities for Aboriginal and Torres Strait Islander people? - Wood, L.; Shilton, Trevor; Dimer, L.; Smith, J.; Leahy, T. (C S I R O Publishing, 2011)
The prevailing disparities in Aboriginal health in Australia are a sobering reminder of failed health reforms, compounded by inadequate attention to the social determinants shaping health and well-being. Discourse around health reform often focuses on the role of government, health professionals and health institutions. However, not-for-profit health organisations are also playing an increasing role in health policy, research and program delivery across the prevention to treatment spectrum. This paper describes the journey of the National Heart Foundation of Australia in West Australia (Heart Foundation WA hereafter) with Aboriginal employees and the Aboriginal community in taking a more proactive role in reducing Aboriginal health disparities, focusing in particular on lessons learnt that are applicable to other non-government organisations. Although the Heart Foundation WA has employed and worked with Aboriginal people and has long identified the Aboriginal community as a priority population, recent years have seen greater embedding of this within its organisational culture, governance, policies and programs. In turn, this has shaped the organisation's response to external health reforms and issues. Responses have included the development of an action plan to eliminate disparities of cardiovascular care in the hospital system, and collaboration and engagement with health professional groups involved in delivery of care to Aboriginal people. Examples of governance measures are also described in this paper. Although strategies and the lessons learnt have been in the context of cardiovascular health disparities, they are applicable to other organisations across the health sector. Moreover, the most powerful lesson learnt is universal in its relevance; individual programs, policies and reforms are more likely to succeed when they are underpinned by whole of organisation ownership and internalisation of the need to redress disparities in health. © 2011 La Trobe University.